1997
DOI: 10.1136/oem.54.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence and mortality around the Pan Britannica Industries pesticide factory, Waltham Abbey.

Abstract: Objectives-To examine the incidence and mortality of cancer near the Pan Britannica Industries factory, Waltham Abbey, after reports of a possible cluster of all cancers and brain cancer in the vicinity. Method-Small area study of cancer incidence 1977-89, and mortality 1981-92, within a 7-5 km radius of the factory site. Postcoded cancer registrations and deaths in the study area were extracted from national data sets held by the Small Area Health Statistics Unit and compared with expected numbers computed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…There is epidemiological evidence to both support and refute the hypothesis that exposure to organochlorines and other environmental compounds acting as weak estrogens or anti-androgens might cause endocrine modulation, as well as produce a variety of adverse effects including potential prostate cancer (Wilkinson et al, 1997;Golden et al, 1998;Miller and Sharpe, 1998;Sonnenschein and Soto, 1998;Parent and Siemiatycki, 2001;Zafar and Terris, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…There is epidemiological evidence to both support and refute the hypothesis that exposure to organochlorines and other environmental compounds acting as weak estrogens or anti-androgens might cause endocrine modulation, as well as produce a variety of adverse effects including potential prostate cancer (Wilkinson et al, 1997;Golden et al, 1998;Miller and Sharpe, 1998;Sonnenschein and Soto, 1998;Parent and Siemiatycki, 2001;Zafar and Terris, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…The general excess in all cancers argues against a specific toxic agent which might be expected to affect the incidence of only one or perhaps a few cancer sites 50. However, epidemiological studies have reported different types of cancer being associated with occupational or residential exposure to oil pollutants 17-23…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, the toxins may pass into the trophic chain, affecting the population. Some authors have already shown associations between colorectal cancer and proximity to industrial pollution sources as metal industries (Garcia-Perez et al, 2010), mining , food and beverage sector and chemical plants (Wilkinson et al, 1997). As regards cement plants, a Brazilian study found a significant elevation on colorectal cancer mortality in an industrialized area with cement industries came into operation in the 1960s, among other facilities (MedradoFaria et al, 2001), and a Korean occupational study suggested a potential association between exposure in the cement industry and an increased risk of rectal cancer (Koh et al, 2013).…”
Section: Installations For the Production Of Cementmentioning
confidence: 99%